2003
DOI: 10.1093/emboj/cdg350
|View full text |Cite
|
Sign up to set email alerts
|

WAVE2 deficiency reveals distinct roles in embryogenesis and Rac-mediated actin-based motility

Abstract: The Wiskott±Aldrich syndrome related protein WAVE2 is implicated in the regulation of actin-cytoskeletal reorganization downstream of the small Rho GTPase, Rac. We inactivated the WAVE2 gene by gene-targeted mutation to examine its role in murine development and in actin assembly. WAVE2-de®cient embryos survived until approximately embryonic day 12.5 and displayed growth retardation and certain morphological defects, including malformations of the ventricles in the developing brain. WAVE2-de®cient embryonic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
177
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(190 citation statements)
references
References 44 publications
12
177
1
Order By: Relevance
“…For example, inactivation of murine WAVE2 is lethal by E12.5 (during mid-gestation) (16); inactivation of N-WASP is lethal at E11.0 (during organogenesis) (33,41); inactivation of Cdc42 is lethal at E3.5 (during implantation) (42); inactivation of Nap1 is lethal at E9.0 (during gastrulation); and inactivation of Rac1 is lethal at E7.5 (during gastrulation) (32,43,44). Abi2 mutants are viable and without morphological defects (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inactivation of murine WAVE2 is lethal by E12.5 (during mid-gestation) (16); inactivation of N-WASP is lethal at E11.0 (during organogenesis) (33,41); inactivation of Cdc42 is lethal at E3.5 (during implantation) (42); inactivation of Nap1 is lethal at E9.0 (during gastrulation); and inactivation of Rac1 is lethal at E7.5 (during gastrulation) (32,43,44). Abi2 mutants are viable and without morphological defects (27).…”
Section: Discussionmentioning
confidence: 99%
“…WAVE1 and WAVE3 were proposed to have roles analogous to WAVE2 in the complex (8). Although the function of WAVE3 is less defined, the critical role of the other two WAVEs in dorsal ruffle formation was demonstrated (15,16). Mechanistically, it is proposed that native WAVE2 complex is inactive (17)(18)(19) but is activated at the membrane by simultaneous interaction with prenylated Rac-GTP and acidic phospholipids as well as by serine/threonine phosphorylation (20).…”
mentioning
confidence: 99%
“…Another group reported that lysates from WAVE2 knockout MEFs, which express other isoforms of WAVEs, do not show Rac-induced in vitro actin polymerization (Yan et al, 2003). In these MEFs, WAVE2 and WAVE1 play roles in cell migration in ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 activates actin polymerization through WASP family verprolin-homologous proteins (WAVE) and Arp2/3 complex leading to formation of membrane ruffles that push the cell membrane forward (Takenawa and Miki, 2001;Suetsugu et al, 2002a). Although WAVEs have been shown to be involved in morphogenesis and motility of cells and in embryonic development of mice (Soderling et al, 2003;Suetsugu et al, 2003;Yamazaki et al, 2003;Yan et al, 2003), their roles in cancer invasion and metastasis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…WASP proteins are dispensable for the formation of lamellipodia (2,3), whereas Wave proteins have emerged as a critical regulator of this structure. In fact, Wave proteins are localized at the tip of the protruding lamellipodium and delocalized whenever this structure retracts (4); genetic inactivation of the ubiquitously expressed Wave-2 gene causes defects in the formation of lamellipodia (5,6). These results highlight the importance of the Wave-Arp2͞3 pathway in the formation of lamellipodia in migrating cells.…”
mentioning
confidence: 99%